Gestión de la producción en la empresa Panecons de la ciudad de Latacunga, diseño de un sistema de gestión de la calidad. - Zambrano León, Víctor Danilo (2014)
This thesis is a Design of the Quality Management and Production Management System based on the ISO 9001:2008 standard, for the company PANECONS S.A. of the city of Latacunga, which provides administrative processes that guarantee its effectiveness and efficiency.